2012
DOI: 10.1111/j.1745-4565.2012.00377.x
|View full text |Cite
|
Sign up to set email alerts
|

INFLUENCE OF MARINE WATER CONDITIONS ON SALMONELLA ENTERICA SEROVAR TYPHIMURIUM SURVIVAL

Abstract: Salmonella enterica serovar Typhimurium strains were isolated during a monitoring survey of the carpet shell clam (Ruditapes decussatus) collected from 23 stations along the Tunisian coast. The effect of starvation on Salmonella Typhimurium survival was investigated in vitro using microcosms composed of filtered (0.2 µm) marine water under dark and ambient temperature conditions (25C for 30 days). Eventual changes in physiological, biochemical properties, serotyping, biotyping and antimicrobial sensitivity for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…DT104 in the EDP phase may have exhibited less resistance to antibiotics due to the loss of plasmids after prolong incubation time and depletion of nutrients. Various studies have reported a modification of the plasmid pattern after long periods of incubation in marine water (Mejri et al., 2012). It is possible that as the cultures continue to grow in the media the oxygen and nutrients become progressively more limited resulting in rendering the EDP cells more sensitive to antibiotics compared to early cells.…”
Section: Discussionmentioning
confidence: 99%
“…DT104 in the EDP phase may have exhibited less resistance to antibiotics due to the loss of plasmids after prolong incubation time and depletion of nutrients. Various studies have reported a modification of the plasmid pattern after long periods of incubation in marine water (Mejri et al., 2012). It is possible that as the cultures continue to grow in the media the oxygen and nutrients become progressively more limited resulting in rendering the EDP cells more sensitive to antibiotics compared to early cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, unlike Haemophilus spp., Salmonella spp. represent a much greater risk to public health, as extended survival in environmental settings, including estuaries such as the Yarra River, has been previously documented [ 66 ] [ 67 , 68 ]. Thus, the risk of infection includes not only those who contact bat faeces directly, but also those who engage in recreational use of the affected waterway.…”
Section: Discussionmentioning
confidence: 99%
“…DT104 in the EDP phase may have exhibited less resistance to antibiotics due to the loss of plasmids after prolong incubation time and depletion of nutrients. Various studies have reported a modification of the plasmid pattern after long periods of incubation in marine water (46). It is possible that as the cultures continue to grow in the media the oxygen and nutrients become progressively more limited resulting in rendering the EDP cells more sensitive to antibiotics compared to early cells.…”
Section: Discussionmentioning
confidence: 99%